2019
DOI: 10.1161/jaha.118.010885
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Aortic Aneurysm Growth in Bicuspid Aortic Valve Patients: Role of Aortic Stiffness and Pulsatile Hemodynamics

Abstract: Background Bicuspid aortic valve ( BAV ) is the most common congenital cardiac abnormality. A thoracic aortic aneurysm ( TAA ) is present in ≈50% of BAV patients, who also have an 8‐fold higher risk of aortic dissection than the general population. Because the health of the aorta is directly reflected in its stiffness and pulsatile hemodynamics, we hypothesized that measures of aortic stiffness and arterial load would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…It is important to contextualize our findings with prior studies that have shown aortic stiffness to be increased in patients with Marfan syndrome, [32,33] and reported increased stiffness to confer risk for aortic dissection [24,34]. Our finding of increased descending aortic distention after proximal aortic graft implantation supports the notion that graft induced changes in aortic physiology are sufficient to overcome intrinsic tissue properties in patients with Marfan syndrome.…”
Section: Plos Onesupporting
confidence: 81%
“…It is important to contextualize our findings with prior studies that have shown aortic stiffness to be increased in patients with Marfan syndrome, [32,33] and reported increased stiffness to confer risk for aortic dissection [24,34]. Our finding of increased descending aortic distention after proximal aortic graft implantation supports the notion that graft induced changes in aortic physiology are sufficient to overcome intrinsic tissue properties in patients with Marfan syndrome.…”
Section: Plos Onesupporting
confidence: 81%
“…The use of indicators such as WSS may be useful to estimate the risk of dilation in BAV patients, by estimating phenotypes with a larger risk for dilation onset and progression. Aortic wall mechanics for BAV patients is fundamentally different than for TAV patients: BAV patients present with ascending aortic wall structural changes resulting in excessive stiffness and reduced compliance in comparison with patients with a normal TAV [71,72]. In fact, a previous study reported a 109.8% increase in the aortic wall stiffness index for BAV patients in comparison with TAV ones [73].…”
Section: Clinical Applicationsmentioning
confidence: 95%
“…Incorporating a non-rigid wall would introduce a range of variables for which data is lacking; this would limit cross-BAV comparisons. In addition, previous studies have showed that the aortic wall in BAV patients presents with excessive stiffness and reduced compliance in comparison with patients with a TAV [71][72][73]. Hence, for these patients, it is preferable to assume the effect of wall motion in velocity and WSS fields as negligible [81].…”
Section: Limitationsmentioning
confidence: 99%
“…5,6 Moreover, approximately 50% of individuals with congenital heart malformations, such as bicuspid aortic valve (BAV), later develop TAA. 7 Yet the origin of the majority of TAA cases remains unknown. It is likely that these cases have more complex origins, involving common genetic variants affecting many genes.…”
Section: Introductionmentioning
confidence: 99%